Tumor cells educate mesenchymal stromal cells to release chemoprotective and immunomodulatory factors. (3rd September 2019) - Le Naour, Augustin; Prat, Mélissa; Thibault, Benoît; Mével, Renaud; Lemaitre, Léa; Leray, Hélène; Joubert, Marie-Véronique; Coulson, Kimberley; Golzio, Muriel; Lefevre, Lise; Mery, Eliane; Martinez, Alejandra; et al.
Abstract: Factors released by surrounding cells such as cancer-associated mesenchymal stromal cells (CA-MSCs) are involved in tumor progression and chemoresistance. In this study, we characterize the mechanisms by which naïve mesenchymal stromal cells (MSCs) can acquire a CA-MSCs phenotype. Ovarian tumor cells trigger the transformation of MSCs to CA-MSCs by expressing pro-tumoral genes implicated in the chemoresistance of cancer cells, resulting in the secretion of high levels of CXC chemokine receptors 1 and 2 (CXCR1/2) ligands such as chemokine (C-X-C motif) ligand 1 (CXCL1), CXCL2, and interleukin 8 (IL-8). CXCR1/2 ligands can also inhibit the immune response against ovarian tumor cells. Indeed, through their released factors, CA-MSCs promote the differentiation of monocytes towards M2 macrophages, which favors tumor progression. When CXCR1/2 receptors are inhibited, these CA-MSC-activated macrophages lose their M2 properties and acquire an anti-tumoral phenotype. Both ex vivo and in vivo, we used a CXCR1/2 inhibitor to sensitize ovarian tumor cells to carboplatin and circumvent the pro-tumoral effects of CA-MSCs. Since high concentrations of CXCR1/2 ligands in patients' blood are associated with chemoresistance, CXCR1/2 inhibition could be a potential therapeutic strategy to revert carboplatin resistance.